"A many‐sided crystal": Understanding the manifold legacy of Silvanus Phillips Thompson (1851–1916). (17th August 2021) - Gooday, Graeme
Abstract: Was Silvanus Phillips Thompson primarily a physicist, electrical engineer, biographer, or teacher? His obituarists could not agree. I argue Thompson was in fact a polymathic generalist who, as a philanthropic Quaker, worked not to promote his own expertise but rather to ensure the public was swiftly informed of the most important techno‐scientific research and applications of his contemporaries. I illustrate this in a comparison of Thompson and his longer‐lived friend Oliver Lodge: working in closely‐related areas, they had contrasting profiles and commitments. After inspecting Thompson's work as textbook author and bibliophile, I resolve his apparently paradoxical status as both radical critic and figurehead of multiple institutions. Finally, to flesh out his friends' representation of him as a "many‐sided crystal, " I analyse Thompson's multi‐facetted posthumous reputation, especially in reviews of the Life and Letters written by his widow Jane and daughter Helen exactly 100 years ago.